(3YbO GdLeGf aj YbO GdQgGf hGdVeGfs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3hHYO agPg eSCdI hbYJ ai GdeMGceGJ hfSCd YfgG aGMHHJ Cf CcJH GdLhGH heG jQO Ydjg djSJaGO aEfgG cKjQI GdhbhY s
(3BNQgG (B:s
(3hGdMeO ddg hMOgq s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3aQZ efg eUfag SfI (B735 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdTGaYjs